Dampak Kecurangan, Kualitas Audit terhadap Nilai Perusahaan dengan Pertumbuhan sebagai Variabel Mediasi - Abdul Kholiq; Ahalik (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam 45, 2025)
Abstract This study aims to understand the effect of fraud, audit quality on firm value mediated by variable growth. This type of research is quantitative, namely data on construction service business companies listed on the IDX in 2018-2023, a total of 21 studies from 22 listed companies, data collection techniques audited financial reports, annual reports and related information. Hypothesis testing using data analysis methods and SEM-PLS analysis SmartPL4 application. Structurally to determine the relationship between fraud, audit quality on firm value mediated by growth. Results: fraud on growth has a significant effect, while audit quality on growth has no significant effect, fraud on firm value has a significant effect, audit quality on firm value has a significant effect, the effect of growth on firm value has a significant effect. While the indirect effect of fraud on firm value through growth is significant, the indirect effect of audit quality on firm value through growth is not significant. For management, investors that fraud has a significant direct impact on firm value, efforts to prevent, detect fraud must be increased because it has a negative impact on investment value, good audit quality is an indicator in assessing the reliability of financial statements. Regulators can use these findings to strengthen regulations related to fraud prevention. Keywords: Fraud, Audit Quality, Growth, Firm Value, Liquidity, Earning Management